Humours as a Vehicle for Discussing Women's Sexuality: A Case Study of Talkpod - Ulfa, Chery Narasyah Chiora; Putri, Seffina Nabilla; Pamuji, Indah Ratri Sekar; Chaerunnisya, Rayoeng Dwi; Nurhadi, Muizzu (Cultural Narratives, 2024)
This research examines the representation of women's sexuality on social media, with a special focus on Indonesian cultural and religious affects. Traditionally, Indonesian women's sexuality has been strongly shaped by social norms that emphasize sexual purity and modesty. But social media has turned into a double-edged sword, allowing people to express themselves while also fostering objectification and. This study uses descriptive qualitative and Sara Mills' Critical Discourse Analysis to examine the sexual objectification of Pamela Safitri, as woman, at the "Talkpod" show. The data came from the conversation between Pamela Safitri and two male hosts. By analyzing interactions between the hosts and Pamela, the study points out the way humour and conversation form and frequently objectify women's sexuality in digital media, especially the reality show that invites women as guest stars. The results of this study explain that sexual objectification of women often uses jokes related to the body both explicitly and implicitly. The findings show that, although social media might empower women, The media is still biased in the discussion of women, especially the sexual objectification of women's bodies through words, sentences, or discourses.